Recruiting foreign nurses for the UK: the role of bilateral labour agreements - Plotnikova, Evgeniya (The University of Edinburgh, 2012)
This thesis is about policy instruments for the regulation of international labour mobility. It focuses on the use of government-to-government agreements on the cross-border movement of nurses, negotiated between source and destination countries. This research is a qualitative case study of agreements signed in the early 2000s between the UK and Spain, South Africa, the Philippines and India. It aims to understand the role of these agreements in British policy as perceived by actors in the destination country. It addresses three questions: 1) What types of agreements did the British government negotiate? 2) Why did the British government negotiate these agreements? and 3) What functions did these agreements perform? Employing the notion of ‘policy tools’ as an organising concept, this thesis’s analytical framework draws on political sociology and the conception of policy instruments as being composed and brought into existence by actors and their power relations in multilevel policy contexts. This study is based on documentary analysis and elite interviews with experts in international organisations, officials in the Department of Health (England), recruitment officers in the source countries, and professional nursing organisations and trade unions in the UK. This thesis argues that government-to-government agreements between the UK and supply countries emerged from a discourse on the ethical recruitment of health workers which was framed in the language of human rights. One of the roles of these agreements was to contain contradictory and conflicting interests between and within institutional actors involved in the international recruitment of nurses on both sides of the migration process. More broadly, the research addresses and advances the discussion of the policy instrumentation approach, and contributes to the understanding of the choice of policy tools and their performance in an ambivalent policy context.
Keywords: health worker migration; policy tools